Co‐implantation of Er and Yb ions into single‐crystalline and nano‐crystalline diamond. (2nd March 2018) - Cajzl, Jakub; Akhetova, Banu; Nekvindová, Pavla; Macková, Anna; Malinský, Petr; Oswald, Jiří; Remeš, Zdeněk; Varga, Marián; Kromka, Alexander
Abstract : The paper reports on the results of Er‐Yb and Er‐Al co‐implantation into commercial single‐crystalline diamonds as well as into nano‐crystalline diamond (NCD) thin films and their photoluminescence properties. The NCD thin films were deposited on fused silica glass by linear‐antenna microwave plasma‐enhanced chemical vapour deposition (PE MWCVD). Er implantation was performed at an energy of 190 keV and fluences of 1 × 10 15 and 5 × 10 15 ions.cm −2 followed by Yb co‐implantation under the same conditions or Al co‐implantation at an energy of 40 keV and the same fluences. The concentration depth profiles of the elements and the degree of their crystal damage (structural ordering) were measured using Rutherford backscattering spectroscopy and Rutherford backscattering spectroscopy/channelling, respectively. Structural changes were studied by Raman spectroscopy. All Er‐Yb doped samples revealed measurable photoluminescence at approximately 1.5 μm. A comparison with Er‐implanted samples showed that the Er‐Yb co‐implantation was beneficial for the photoluminescence at 1.5 μm in both substrates. Er‐doped NCD films revealed higher intensity of luminescence than Er‐doped single‐crystal diamond. This observation is attributed to the specific incorporation of Er into the diamond and at the grain boundaries.